ASSESSMENT OF STABILITY OF BACTERIOCIN ISOLATED FROM GUT PROBIOTICS OF AN INDIAN FRESHWATER FISH, L. rohita - V. SUMATHI; D.C. REDDY; V. KALARANI (International Journal of Pharma and Bio Sciences, 2016)
Probiotic bacteria produce a variety of antimicrobial substances such as short chain fatty acids, Nitric acid, Hydrogen peroxide, Bacteriocins etc. Bacteriocins, the ribosomally synthesized peptides, are known to exhibit bactericidal activity through a transmembrane pore – forming mode of action aganist pathogens. In the present study small molecular weight peptide (Bacteriocin) was isolated from Bacillus subtilis and Terribacillus saccharophillus, the gut wall inhabiting bacteria of L. rohita. The bacteriocin was found to have a significant inhibitory action against Vibrio harveyi, Pseudomonas fluorescens, Aeromonas hydrophila and Escherichia coli. Further it was detected to have stable activity against Aeromonas hydrophila within the temperature range of 37 to 1000C, pH of 2 to 10 and 5 to 10% Tween 80 (surfactant). Thus the bacteriocins produced by B. subtilis and T. saccharophillus may have potentially suitable for use in food preservation industry.